SOCIO-ECONOMIC AND DEMOGRAPHIC PROFILE OF ADOLESCENT MOTHERS - Sonia Maria Könzgen Meincke; Mayza Raphaella Pontes de Oliveira; Débora Raquel Soares Guedes Trigueiro; Telma Elisa Carraro; Emilainne Trindade Cavalcanti Gondim; Neusa Collet (Universidade Federal do Paraná, 2011)
The objective was to describe the socio-economic and demographic profile of adolescents in the maternity ward of a university hospital in Paraíba. This quantitative study was carried out between December 2008 and November 2009, by means of a structured questionnaire given to 85 adolescent expectant mothers. The principle variables analyzed were: age, colour, occupation, marital status, educational level, family income and the support the expectant mother received. The program Statistical Package for the Social Sciences was used for the analysis. The results indicate that the adolescents are dark-skinned (69.4%), with low levels of schooling (61.2%) and high levels of truancy (73.8%) and unemployment (92.9%). They are economically dependent (89.4%), and belong to less-favoured economic classes. This reality contributes to the continuation of the cycle of poverty. Unplanned pregnancy in adolescence creates consequences for the adolescent, her family and society. The importance of family and social support as protective factors was clear.